2020
DOI: 10.1002/fsn3.1548
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and anti‐atherogenic activities of crude polysaccharides from abalone viscera

Abstract: This study was performed to evaluate the hypolipidemic and anti‐atherogenic activities of the crude polysaccharides extracted from abalone viscera (AVCP). The major functional groups of purified polysaccharides were analyzed by infrared spectroscopy (IR). Male Kunming mice (SPF) were divided into six groups and were treated with normal diet or high‐fat diet with AVCP or Xuezhikang (hypotensive drug) for 5 weeks. Physicochemnical analysis of AVCP showed the presence of 60.4% polysaccharides, 17.9% protein, 6.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…MSP from Cystoseira crinita could inhibit lipase activity in plasma and small intestine, leading to a significant decrease in blood triglyceride in rats fed a high fat diet [51]. In mice induced by high fat diet, it was found that polysaccharides from abalone viscera not only decreased blood lipid but also significantly increased the activity of malondialdehyde and superoxide dismutase, suggesting that it might play a role in the antioxidant pathway to improve the lipid metabolism disorder [52]. Ethanol extract from Hypnea musciformis could modulate lipid peroxidation in mammary carcinogenesis [53].…”
Section: Regulating Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…MSP from Cystoseira crinita could inhibit lipase activity in plasma and small intestine, leading to a significant decrease in blood triglyceride in rats fed a high fat diet [51]. In mice induced by high fat diet, it was found that polysaccharides from abalone viscera not only decreased blood lipid but also significantly increased the activity of malondialdehyde and superoxide dismutase, suggesting that it might play a role in the antioxidant pathway to improve the lipid metabolism disorder [52]. Ethanol extract from Hypnea musciformis could modulate lipid peroxidation in mammary carcinogenesis [53].…”
Section: Regulating Lipid Metabolismmentioning
confidence: 99%
“…A fraction named AGP33 with sulfates occur at 3-O-and 4-O-positions showed a better anticoagulant activity than its desulfated product [93]. MSPs from abalone viscera also exhibited significantly hypolipidemic and anti-atherogenic activities [52]. Another abalone SP (AGSP) and its desulfated product D-AGSP can inhibit fat accumulation and improve lipid metabolism balance and gut microbiota dysbiosis in mice fed with high fat diet [94].…”
Section: Role Of Sulfate Group and Sulphation Patternmentioning
confidence: 99%
“…Numerous studies have demonstrated, large amounts of bioactive compounds like polysaccharides extracted from natural resources can ameliorate lipid metabolic disorders due to their high efficacy against hyperlipidemia and their little or none adverse side effects (L. Li & W. Guo et al., 2019 ; Xie et al., 2016 ). Crude polysaccharides extracted from abalone viscera reduce lipid levels in plasma and show antiatherogenic activity in a mouse model of a lipid disorder (Liu et al., 2020 ). The sulfated polysaccharides from Cytosmear crinite induced a decrease in low‐density lipoprotein (LDL) and triglycerides (TG) and an increase in high‐density lipoprotein (HDL) blood levels in high‐fat diet rats (Ben Gara et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…anti-atherogenic, antitumor, antiviral, and immunomodulation activities (Ferreira et al, 2015;Martins et al, 2017;Liu et al, 2020).…”
mentioning
confidence: 99%